2018
DOI: 10.1016/j.heliyon.2018.e00798
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and optimization of lucky nut biodiesel production from lucky nut seed by pearl spar catalysed transesterification

Abstract: In 2015, the Worldatlas recorded 50 countries whose source of income is fossil fuel and its derivatives. Surprisingly, these countries solely depend on this source of energy up to 100% (Omar, Qatar, Kuwait and Saudi Arabia) because of technology improvement. It's so sadden that apart from its adverse effect on the economics of the countries, fossil fuels harmful effects on the universe cannot be overlooked. Meanwhile, the use of renewable energy as a replacement for fossil fuel and its derivatives are faced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…Also, comparative analysis of the capability of RSM and ANFIS-GA as well as ANFIS/ANN on predicting the oil yield from hura crepitans has been studied ( Ropo et al, 2020 ; Nwosu-Obiegu et al, 2020 ). The application of RSM and ANN for the optimization of oil extraction from gmelina ( Uzoh and Onukwuli, 2016 ), lucky nut ( Adepoju et al, 2018 ) and hevea brasiliensis ( Onoji et al, 2017 ) has equally been reported. It is therefore, evident that although previous researches have proven that the RSM and ANN-GA techniques are always complimentary ( Betiku et al, 2018 ), the comparative assessment of RSM and ANN-GA for oil extraction has scarcely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Also, comparative analysis of the capability of RSM and ANFIS-GA as well as ANFIS/ANN on predicting the oil yield from hura crepitans has been studied ( Ropo et al, 2020 ; Nwosu-Obiegu et al, 2020 ). The application of RSM and ANN for the optimization of oil extraction from gmelina ( Uzoh and Onukwuli, 2016 ), lucky nut ( Adepoju et al, 2018 ) and hevea brasiliensis ( Onoji et al, 2017 ) has equally been reported. It is therefore, evident that although previous researches have proven that the RSM and ANN-GA techniques are always complimentary ( Betiku et al, 2018 ), the comparative assessment of RSM and ANN-GA for oil extraction has scarcely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Ikbal et al (2018) [7] reported the practice of discarded snail shells as a heterogeneous catalyst for the synthesis of biodiesel from soybean oil, while in 2019, Subramaniapillai [8] and co used Donax delltoides shell as heterogeneous catalyst. The use of pearl spar as a heterogeneous catalyst was employed in the study reported by Adepoju et al (2018) [9], while in another work, Betiku et al (2015) [10] developed heterogeneous catalyst from plantain peel, applied it to biodiesel synthesis from yellow oleander. The study conducted in another work by Betiku et al (2017) [11] reported the use of heterogeneous catalyst developed from cocoa pod husks, while Nath et al (2019) [12] developed heterogeneous catalyst from waste Brassica nigra plant for biodiesel production.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Ikbal et al [7] reported the practice of discarded snail shells as a heterogeneous catalyst for the synthesis of biodiesel from soybean oil, while in 2019, Subramaniapillai et al [8] used Donax delltoides shell as heterogeneous catalyst. The use of pearl spar as a heterogeneous catalyst was employed in the study reported by Adepoju et al [9], while in another work, Betiku et al [10] developed heterogeneous catalyst from plantain peel, applied it to biodiesel synthesis from yellow oleander. The study conducted in another work by Betiku et al [11] reported the use of heterogeneous catalyst developed from cocoa pod husks, while Nath et al [12] developed heterogeneous catalyst from waste Brassica nigra plant for biodiesel production.…”
Section: Introductionmentioning
confidence: 99%